Sustainable Procurement Practice in Ghana Health Service - Doh, Zebaot Kwadzo (2015)
A Thesis submitted to the Department Of Building Technology, Kwame Nkrumah University Of Science And Technology in partial fulfillment of the requirements for the degree of Masters of Science (MSc.) in Procurement management.